An isotope dilution-liquid chromatography-tandem mass spectrometry-based candidate reference measurement procedure for the quantification of piperacillin in human serum and plasma - Sandra Fleischer; Judith Taibon; Neeraj Singh; Carina Schuster; Arber Rexhaj; Michael Vogeser; Friederike Bauland; Andrea Geistanger; Elie Fux (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Objectives Piperacillin is a broad-spectrum antibiotic used to treat critically ill patients with severe infections, requiring therapeutic drug monitoring (TDM). We report the development of an isotope dilution-liquid chromatography-tandem mass spectrometry-based candidate reference measurement procedure (RMP) to quantify piperacillin in human plasma and serum. Methods Primary reference material was characterized by quantitative nuclear magnetic resonance (qNMR) to ensure traceability to the International System of Units (SI). Piperacillin was analyzed using LC-MS/MS operating in positive electrospray ionization and multiple reaction monitoring mode. Method validation evaluated selectivity, matrix effects, precision, accuracy, and measurement uncertainty (MU) according to GUM guidelines. Results This RMP allowed quantification of piperacillin within the range of 0.773 µmol/L (0.400 µg/mL) to 464 µmol/L (240 µg/mL), with selectivity, sensitivity and matrix-independence. Intermediate precision was